Dados históricos da produção de sementes de soja na unidade de Campo Mourão da Coamo Agroindustrial Cooperativa - Abreu, Marcelo Cordeiro de (2008)
Ranked second world producer, Brazil has the highest soybean plantation area in grain cultivated land. This fact is especially true on the arrival of transgenic seeds which introduces genes from different species of soybean into its genome. Seed quality, an extremely important item, may be affected by different factors which may occur before and after harvest, and during all the production stages, such as drying, industrialization, storing, transport and sowing. Current research evaluates commercialization of soybean seed at the Coamo Agricultural and Industrial Cooperative of Campo Mourão PR Brazil with regard to the product s processing and the efficiency of the quality process in seed production. Quality and quantity data on the case study refer to seed production in the years 2004 - 2005, 2005 - 2006 and the 2006 2007 harvest. Results show that cleaning processing and total seed usage indicated growth between 2004 - 2005 and 2006 - 2007, respectively, from 59.41% and 45.69% to 69.79% and 64.82%. A higher percentage of transgenically modified cultivars (RR) occurred in seed production during the 2004 2005 harvest. Varieties represented 11.67% of total processed seeds which reached 42.68% in the 2006 2007 harvest. Process may improve by technical follow-up ranging from seedling to harvest time.